Microstructural and Tribological Behavior of Pulse Electroplated Nickel Barrier on Copper Conductors - Sharma, Ashutosh; Ahn, Byungmin (Tribology Transactions, 2019)
The microstructural, mechanical, and tribological behaviors of electroplated Ni on Cu conducting substrates have been investigated in this study. The microstructural studies were performed by X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM). The results showed that initially (111) with (220), (200) Ni texture components were predominant in the coating, and increasing the current density from 0.1 to 0.5 A/cm2 led to the development of a strong (111) texture. The presence of ultrafine grains coupled with a (111) Ni texture improved the coating microhardness and wear properties significantly. It was shown that with an increase in current density, wear resistance of the coatings improved significantly and the electrical resistivity increased due to the highly populated grain boundaries.
Keywords: Conducting substrates; Copper conductors; Electroplated Ni; Electroplated nickel; Micro-structural; Texture components; Tribological behaviors; Ultra fine grain; current density; Electroplating; friction; microhardness; nickel; resistivity; wear